The Determinants Indonesia Composite Index on the Indonesia Stock Exchange - Wahasusmiah, Rolia (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This study aimed to determine and analyze the movement of the composite stock price index by observing the variables of inflation, exchange rates, interest rates, and the amount of money circulating in companies listed on the Indonesia Stock Exchange. The population in this study is all monthly time series data, including the Composite Stock Price Index (CSPI) for the period January 2019 to December 2020, with as many as 24 months of observation for each variable. The sample selection method uses a saturated sample because the Composite Stock Price Index includes the average stock price of all companies listed on the Indonesia Stock Exchange. The data were processed by quantitative descriptive techniques using multiple linear regression statistical tests. The results of this study indicate that inflation and interest rates positively affect the Composite Stock Price Index. Meanwhile, the Exchange Rate and the Money Supply have no effect on the Composite Stock Price Index on the Indonesia Stock Exchange. In the Covid-19 pandemic, economic growth slowed, causing the Indonesian economy to decline.